Cycles of Transient High-Dose Cyclophosphamide Administration and Oncolytic Adenovirus Vector Intratumoral Injection for Long Term Tumor Suppression in Syrian Hamsters - Dhar, Debanjan (2014)
Immune responses against oncolytic adenovirus (Ad) vectors are thought to limit vector anti-tumor efficacy. In Syrian hamsters, which are immunocompetent and whose tumors and normal tissues are permissive for replication of Ad5-based oncolytic Ad vectors, treating with high-dose cyclophosphamide to suppress the immune system and exert chemotherapeutic effects enhances Ad vector anti-tumor efficacy. However, long term cyclophosphamide treatment and immunosuppression can lead to anemia and vector spread to normal tissues. Here we employed three cycles of transient high-dose cyclophosphamide administration plus intratumoral injection of the oncolytic Ad vector VRX-007 followed by withdrawal from cyclophosphamide. Each cycle lasted 4-6 weeks. This protocol allowed the hamsters to remain healthy so the study could be continued for ~100 days. The tumors were very well suppressed throughout the study. With immunocompetent hamsters, the vector retarded tumor growth initially, but after 3-4 weeks the tumors resumed rapid growth and further injections of vector were ineffective. Preimmunization of the hamsters with Ad5 prevented vector spillover from the tumor to the liver yet still allowed for effective long term anti-tumor efficacy. Our results suggest that a clinical protocol might be developed with cycles of transient chemotherapy plus intratumoral vector injection to achieve significant anti-tumor efficacy while minimizing the side effects of cytostatic treatment.